Pengembangan E-Modul pada Mata Pelajaran Sistem Komputer untuk Kelas X Program Keahlian Teknik Komputer dan Jaringan di SMK Negeri 2 Malang dengan Model Pengembangan 4-D - Rizka Hikma Damayanti; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Vocational High School 2 Malang has a number of expertise programs, one of which is Computer and Network Engineering. When learning, students are not given a module, the teacher uses teaching methods using powerpoint teaching media. One solution that can be used to solve this problem is to develop learning media in the form of E-Modules. With the hope that the E-Module can motivate and attract students' attention to the material presented. The development of E-Modules is carried out using a 4-D development model because it is suitable for the development of teaching devices. Data collection methods are used in the form of interviews, questionnaires and tests. Based on the questionnaire, the validation test of media experts and material experts shows that learning media in the form of E-Modules are declared to be very valid and suitable for use in the teaching process with an overall average percentage of material experts at 98.96% and media experts at 80.00% . The results of the pre-test conducted by 31 students received an average of 50.45 and an average post-test score of 91.74. In addition, the results of the t-test obtained a significance value of less than 0.05 which is equal to 0,000. From the results obtained from the analysis, it can be concluded that learning media in the form of E-Modules that have been developed can be used effectively in the teaching process.